2014
DOI: 10.1098/rspa.2014.0094
|View full text |Cite
|
Sign up to set email alerts
|

Cellular buckling in stiffened plates

Abstract: An analytical model based on variational principles for a thin-walled stiffened plate subjected to axial compression is presented. A system of nonlinear differential and integral equations is derived and solved using numerical continuation. The results show that the system is susceptible to highly unstable local-global mode interaction after an initial instability is triggered. Moreover, snap-backs in the response showing sequential destabilization and restabilization, known as cellular buckling or snaking, ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 22 publications
(55 reference statements)
4
51
0
Order By: Relevance
“…I-section struts [10,22] and stiffened plates [11]. These analytical models show very good quantitative comparisons with FE results and existing experimental results [9].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…I-section struts [10,22] and stiffened plates [11]. These analytical models show very good quantitative comparisons with FE results and existing experimental results [9].…”
Section: Introductionmentioning
confidence: 52%
“…Since previous studies [31,32,10,11,26,27] have clearly demonstrated that it is essential to include the shear strain contributions into the total potential energy formulation to model the interactive buckling behaviour, Timoshenko beam theory is assumed currently. The global mode is decomposed into two components: a pure lateral displacement W and a pure rotation of the plane sections θ, see Figure 2, known as the 'sway' and 'tilt' modes [33,31] respectively.…”
Section: Modal Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, for L < L l , the strut exhibits pure local buckling of the flange plates that is strongly stable. Note that for L l < L < L o , all interactive post-buckling equilibrium paths exhibit the sequential snap-backs signifying cellular buckling behaviour [11,7,6].…”
Section: Pinned Flange-web Jointmentioning
confidence: 99%
“…Structural members made from slender plate elements entirely under compression, or in part, are well known to be susceptible to a variety of different elastic instability phenomena [1,2,3,4,5,6,7,8,9,10]. In recent works [11,12], a variational model representing an open and doubly-symmetric thin-walled I-section strut under axial compression, made from a linear elastic material, was introduced where both local or global buckling could occur first.…”
Section: Introductionmentioning
confidence: 99%